Determination of oral bioavailability of herbal components in mice. - Weng, Luwei. (2013)
SFBK and BKSF which derived from DALK by grafting onto the secondary loop and binding loop of SFTI respectively are two novel orally active drugs applicable for inflammatory pain killing by their high binding affinity to BK1 receptors. In this study, both SFBK and BKSF were orally administrated to mice by gavaging and blood samples were collected every an hour after 2h postdose. Sample preparation was done by peptide extraction in 100% ethanol and using Gemfibrozil as internal standard. Reverse-phase high-performance liquid chromatography (RP-HPLC) was conducted to measure the pharmacokinetic parameters and bioavailability of these two drugs. Both the SFBK and BKSF have a relatively high stability in mice plasma and can be active in plasma for approximately 5 hours after administration.